Weaponizing Culture: The Role of Illiberal Cultural Policy in Slovenia’s Democratic Backsliding - Kristina Čufar; Hana Hawlina (Politics and Governance, 2025)
The weaponization of cultural policy is one of the crucial, yet underexplored strategies of illiberal political actors. This article investigates the multifaceted illiberal cultural policy measures employed to polarize society, influence the interpretation of history, consolidate so‐called traditional values and ethnonationalism, and normalize political corruption and increasingly authoritarian political practices. The analysis and typology of illiberal cultural policy measures are based on the case study of a period of extreme illiberalization in Slovenia between 2020 and 2022, which was characterized by overt and frequent political interventions in the artistic and cultural sphere. Rather than treating them as isolated incidents, the article traces their cumulative desired and actual effects, as well as the resistance they provoked. Based on the analysis of the Slovenian case, we propose a typology of illiberal cultural policy measures that is applicable to other contexts experiencing democratic backsliding. Illiberal political actors recognize the significance of art and culture as either the means of reinforcing illiberal ideology and political aims or the site of democratic resistance. By targeting the cultural sphere, illiberal political actors pursue the double goal of amplifying expedient narratives and silencing dissent. Increasing political control over cultural production thus curtails the space for democratic deliberation and permanently reshapes the socio‐political landscape. Considering illiberal cultural policy as a pivotal strategy for the indelible transformation of political ideology and practice reveals an important dimension of democratic backsliding and the success of illiberal politics in Europe and beyond.